Legal Review of the Practice of Paying Lecturers Below Minimum Standards in Private Higher Education Employment Contracts - Amalia, Apri; Turnip, Johannes Mangapul; Saputra, Jarnawi Hadi (IHSA Institute, 2025)
Lecturers are not only teachers, but also have a role as researchers and implementers of community service. Therefore, lecturers are entitled to receive a decent wage in accordance with minimum standards. The employment relationship between lecturers and Private Higher Education Institutions (PTS) is outlined in the form of an employment agreement that includes concise provisions regarding rights and obligations, one of which is the right to Lecturer Wages. In practice, there are several lecturers in the Private Higher Education environment who have not enjoyed their wage rights optimally. They receive wages below the minimum standard, paid according to per credit unit of teaching, which is not in accordance with the lecturer employment agreement and laws and regulations. This raises issues regarding the legality of the lecturer employment agreement system in PTS and the legal protection of lecturers against substandard wages. This study aims to determine the wage system of lecturers' employment agreements with private universities (PTS) and analyze legal protection against wage practices that do not comply with regulations. The research method used is normative juridical with a statutory approach and literature review. The results of the study indicate that the implementation of fixed-term employment agreements between lecturers and private universities does not comply with the provisions of Articles 90 and 91 of the Manpower Law, which state that wages below the Provincial Minimum Wage (UMP) are invalid. This violation has legal consequences in the form of default and administrative sanctions. Legal protection for minimum wages is affirmed in Government Regulation No. 36 of 2021 concerning Wages, which regulates the wage scale structure, and Regulation of the Minister of Education, Culture, Research, and Technology No. 53 of 2023